Aktywna rola transportu w warunkach gospodarki socjalistycznej - Stęplowski, Bronisław (Wydział Prawa i Administracji UAM, 1967)
The correct functioning of a transport system can incite the development of commodity exchange and in this way influence processes of production. Situated in an area of possible potential production an adequate transport network can become the deciding factor in the development of the area. Easy accessibility to the network facilitates greater commodity exchange, wider marketing area and consequently creates a basis for introducing advantageous social changes in production processes — widening its volume, assortment changes, higher degree of specialization. The active role of transport in economy lies therefore in the utilization of convenient transport conditions, stimulating in this way commodity circulation and encouraging the introduction of changes in production itself. An indispensible condition for the functioning of 'this transport is the anticipation of an increased transport efficiency in the area. The possibility of the active influence of transport on other sections is seen in the concept of "social costs of functioning" of transport. Apart from the investments effectively borne in transport to the above concept should be added the additional alternative costs, that is to say dependent on the activity of transport but in the section making use of transport services. Transport can also have an influence on socialist economy. The planning charakter of economy limits this influence but does not exclude it. Apparently in socialist economy the influence of transport on the development of exchange and production is dependent to, a certain extent, on the existing model of economic management. In a centralized model the range of this influence is less. The central organ of economy undertaking almost all decisions can directly apply transport efficiency to effective demand. In a decentralized model the range of active influence of transport is greater. Activization of regions, development of some branches of production such as agriculture, regional industry, trade, depends in this case on the decision of lewer units of economy — enterprises, associations and regional administration organs. Central organs of planning endeavouring to initiate definite processes of economy in a certain region can, thrugh the development of a transport network, create convenient conditions of transport and in this way encourage enterprises to expand — widen the marketing area, greater production etc. To fulfill this task the development of a transport network must anticipate the needs for service. In this connection transport efficiency not fully utilized temporarily should not be considered wasted. In the long run the additional cost of temporarily frozen assets is compensated by the advantages of exchange in production dependent on previously installed transport base. Comparing the long-term tendency of developing production and commercial transport and the dynamic investments in both spheres shows however, that in the present economic situation in Poland, the technical equipment of transport is not sufficient enough to be able to have a stimulating influence , on the development of production and exchange.
The active role of transport in socialist economy